2011
DOI: 10.1007/s13213-011-0238-1
|View full text |Cite
|
Sign up to set email alerts
|

High-level tannase production by Penicillium atramentosum KM using agro residues under submerged fermentation

Abstract: A tannase-yielding fungal strain identified as Penicillium atramentosum KM was isolated from tannery effluent collected from a small-scale tannery. The fungal strain produced extracellular tannase under submerged fermentation (SmF) using amla (Phyllanthus emblica), ber (Zyzyphus mauritiana), jamoa (Eugenia cuspidate), jamun (Syzygium cumini) and keekar (Acacia nilotica) powdered leaves. Among the different substrates, amla and keekar leaves resulted in maximal extracellular production of tannase. Various proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…The three-dimensional plot shows the infl uence of incubation temperature and pH on tannase production 4.5 and 6.0 for tannase production by Paecilomyces variotii. Selwal and Selwal (38) studied Penicillium atramentosum tannase and found that the enzyme exhibits optimal activity at pH=7.5.…”
Section: Optimization Of Temperature and Ph For Tannase Productionmentioning
confidence: 99%
“…The three-dimensional plot shows the infl uence of incubation temperature and pH on tannase production 4.5 and 6.0 for tannase production by Paecilomyces variotii. Selwal and Selwal (38) studied Penicillium atramentosum tannase and found that the enzyme exhibits optimal activity at pH=7.5.…”
Section: Optimization Of Temperature and Ph For Tannase Productionmentioning
confidence: 99%
“…In 2012, Selwal & Selwal [7] evaluated tannase production by a strain of P. atramentosum from tannery effluents in SSF using amla, jujube, jambul, Syzygium sp., and kikar leaves. The authors observed maximum tan-nase yields of 170.75 and 165.56 U/g dry tissue from jambul and kikar leaves, respectively, incubated at 28˚C for 96 h. The form of showed of the results of this study are different from literature, as presented in U/mL, numerically lower results are to be compared with these data.…”
Section: Discussionmentioning
confidence: 99%
“…For example, many agro-industrial wastes are commonly discarded into the environment untreated [11]. In this context, solid-state fermentation (SSF) by fungi presents an excellent alternative for producing tannase while simultaneously reducing waste [7]. Because filamentous fungi grow in nature in solid substrates, such as wood, roots, stems, and leaves of plants, in the absence of free water [12].…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme production by fungi is commonly performed by solid-state fermentation, submerged fermentation or surface-adhesion fermentation (MacCabe et al, 2002;Elisashvili et al, 2008;Correa et al, 2012;Selwal and Selwal, 2012). However, biotechnological processes with immobilized growing fungi cells, including those for extracellular enzyme production, seem to be more favorable than traditional fermentation methods since immobilization enables repetitive and continuous use of the microbial cells (Correa et al, 2012).…”
Section: Full Papermentioning
confidence: 99%